Amino Sugar-Enriched Fraction of Korean Red Ginseng Extract Induces the Priming Step of NLRP3 Inflammasome - Huijeong Ahn; Geun-Shik Lee (Molecules, 2024)
Intracellular protein complexes, known as inflammasomes, activate caspase-1 and induce the secretion of pro-inflammatory cytokines, namely interleukin (IL)-1β and -18. Korean Red Ginseng extract (RGE) is a known immunomodulator and a potential candidate for the regulation of inflammasomes. The saponins, such as ginsenosides, of RGE inhibit inflammasome signaling, while non-saponin substances containing amino sugars promote the priming step, up-regulating inflammasome components (pro-IL-1β, NLRP3, caspase-1, and Asc). In this study, the amino sugar-enriched fraction (ASEF), which increases only non-saponin components, including amino sugars, without changing the concentration of saponin substances, was used to investigate whether saponin or non-saponin components of RGE would have a greater impact on the priming step. When murine macrophages were treated with ASEF, the gene expression of inflammatory cytokines (IL-1α, TNFα, IL-6, and IL-10) increased. Additionally, ASEF induced the priming step but did not affect the inflammasome activation step, such as the secretion of IL-1β, cleavage of caspase-1, and formation of Asc pyroptosome. Furthermore, the upregulation of gene expression of inflammasome components by ASEF was blocked by inhibitors of Toll-like receptor 4 signaling. Maltol, the main constituent of ASEF, promoted the priming step but inhibited the activation step of the inflammasome, while arginine, sugars, arginine–fructose–glucose, and fructose–arginine, the other main constituents of ASEF, had no effect on either step. Thus, certain amino sugars in RGE, excluding maltol, are believed to be the components that induce the priming step. The priming step that prepares the NLRP3 inflammasome for activation appears to be induced by amino sugars in RGE, thereby contributing to the immune-boosting effects of RGE.